NEW SCHWARZ NORMS ON B(H) - Okwany, I. O.; Rao, G. K. R.; Manyonge, Alfred; Okelo, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
In this paper, we give results on new Schwarz norms in B(H). We also give acharacterization for a new class of norms in Banach space setting.